The Anas bin Malik Assembly plays an Important Role in Building Social Relationships in Kanjilo Village, Barombong District, Gowa Regency. - Sarjayani, Andi Panca (Jurnal Mercusuar, 2020)
Majelis Taklim is a forum for conducting da’wah activities. The function and role of Majelis Taklim can be seen from its activities. The results of this study indicate that there are several roles of (MT) Anas Bin Malik in fostering community relationships in Kanjilo Village, Barombong District, Gowa Regency, including: conducting joint recitation and dhikr, engaging in community service, visiting those affected by calamities, commemorating Islamic holidays, commemorating Isra Mi’raj, conducting community service, and managing funerals. The supporting factors for (MT) Anas Bin Malik include cooperation between members and the community, while the inhibiting factors include time constraints such as lack of community participation due to outside engagements such as family events, inadequate facilities and infrastructure, and the fact that many residents still engage in ancestor worship practices, such as holding a feast at a cemetery